Patient and Provider Demographics and the Management of Genitourinary Tract Infections in the Emergency Department - Johnathan M. Sheele; Lanyu Mi; Jessica Monas; Michael Mohseni (Emergency Medicine International)
Introduction. Urinary tract infections (UTIs) and sexually transmitted infections (STIs) can have overlapping signs, symptoms, and findings on urinalysis. Our objective was to determine if patient or provider demographics are associated with differences in the diagnosis and management of UTIs and STIs in the emergency department (ED). Methods. We analyzed 38,062 ED patient encounters from a single healthcare system between April 18, 2014, and March 7, 2017. All encounters were women ≥18 years of age and not admitted to the hospital. We performed logistic regression using patient and provider demographics, laboratory testing results, ED triage data, and ED diagnoses. Results. The patient’s age, race, and marital status were not associated with having an ED UTI diagnosis with a urine culture ≥10,000 colony forming units (CFUs)/mL (vs. <10,000 CFUs/mL). Patient race and the sex of the ED provider were not associated with differences in empiric antibiotic treatment for gonorrhea and chlamydia during the ED encounter. Patient’s race and the sex of the ED provider were also not associated with discordance between empiric antibiotic therapy given in the ED and the results of gonorrhea and chlamydia tests that resulted following the ED encounter. Conclusion. In our multivariate analyses, we did not observe that the patient’s race resulted in significant differences in the diagnosis of UTIs with bacteriuria ≥10,000 CFU/mL or differences in the empiric treatment of gonorrhea and chlamydia infections among those tested for the infection in the ED. The patient’s age and marital status, but not the provider’s sex, were significantly associated with differences in the management of gonorrhea and chlamydia.